Respuesta :
Answer: x = 4
Explanation: root x-1 = 2- root x+3
First let’s take out the root by square both side by 2 we get:
x-1= 4-x+3
x-1 = -x+7
x+x = 7+1
2x= 8
x= 8/2=4
Explanation: root x-1 = 2- root x+3
First let’s take out the root by square both side by 2 we get:
x-1= 4-x+3
x-1 = -x+7
x+x = 7+1
2x= 8
x= 8/2=4
Answer:
[tex]x=1[/tex]
Step-by-step explanation:
[tex]\sqrt{x-1} =2-\sqrt{x+3}[/tex]
Square both sides.
[tex]\left(\sqrt{x-1}\right)^2=\left(2-\sqrt{x+3}\right)^2[/tex]
[tex]x-1=x+7-4\sqrt{x+3}[/tex]
Subtract x on both sides.
[tex]x-1-x=x+7-4\sqrt{x+3}-x[/tex]
[tex]-1=-4\sqrt{x+3}+7[/tex]
Subtract 7 on both sides.
[tex]-1-7=-4\sqrt{x+3}+7-7[/tex]
[tex]-8=-4\sqrt{x+3}[/tex]
Square both sides.
[tex]\left(-8\right)^2=\left(-4\sqrt{x+3}\right)^2[/tex]
[tex]64=16x+48[/tex]
Subtract 48 on both sides.
[tex]64-48=16x+48-48[/tex]
[tex]16=16x[/tex]
Divide both sides by 16.
[tex]\frac{16}{16} =\frac{16x}{16}[/tex]
[tex]1=x[/tex]
Switch sides.
[tex]x=1[/tex]